Determinants of buying intention of halal products on private Islamic religious college lecturers in West Java - Husaeni, Uus Ahmad; Zakiah, Selviana (Faculty of Business & Economics, Universitas Islam Indonesia, 2022)
Purpose − This study aims to analyze the factors influencing the buying intention of halal products at Private Islamic Religious College (PTKIS) Lecturers in West Java.Methodology − The population in this study were Private Islamic Religious College (PTKIS) lecturers located in the West Java region of West Priangan, including the Cianjur Regency, Sukabumi Regency, and Bogor Regency. The number of PTKIS Lecturers in the Cianjur Regency filled out the questionnaire was 78. 83 Lecturers in Sukabumi District and 105 in Bogor District were used as research samples. Meanwhile, the data analysis technique used multiple linear regression.Findings − Halal certification affects buying intention of halal products at PTKIS Lecturers in Cianjur, Sukabumi, and Bogor Regencies. Halal awareness only affects Cianjur and Bogor Regencies. Meanwhile, in Sukabumi Regency, the effect was not significant. Food composition has an impact in Sukabumi District, but it does not substantially influence Cianjur and Bogor Regencies.Implication − Producing or selling food for producers needs to consider three factors: halal certification, awareness, and food ingredients. Consumers must pay attention to the halal logo to ensure that the products consumed are truly halal and follow Islamic teachings.Originality − Halal certification is an essential key for business product development. Meanwhile, most lecturers do not use food composition as the primary reference in choosing halal products to buy. Halal awareness of PTKIS lecturers has different perceptions.